Analisis SWOT terhadap Strategi Pemasaran Syariah pada WM Boutique di Kabupaten Gowa - Lisa Indryawati Lisa; Idris Parakassi; A. Syathir Sofyan (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The purpose of this research is to analyze the marketing strategy implemented by WM Boutique so that it can grow very rapidly at this time by using SWOT analysis. This study uses a combined research method. Mixed methods are meant to use qualitative and quantitative methods. Mixed methods research aims to answer research questions that cannot be answered by a qualitative or quantitative approach alone. This research focuses on the collection, analysis, and mixing of quantitative and qualitative data in one or a series of studies. The results of this study show how the sharia marketing strategy implemented by WM Boutique, namely improving product quality, strategic and convenient location and maximizing promotions and based on SWOT analysis it is known that WM Boutique is in quadrant I by implementing an aggressive strategy. Quadrant I is a very profitable situation, the company has opportunities and strengths so that it can take advantage of existing opportunities. The strategy that must be applied in this condition is to support an aggressive growth policy (growth oriented strategy), it is recommended to maximize the opportunities and strengths that exist.